Corporate Social Responsibility and Culture: The case of the largest Greek Commercial Bank. - Kinias, Ioannis G.; Agrogiannis, Serafim; Bolla, Eirini (Archives of Business Research, 2017)
Throughout the years, the banking sector has encountered many challenges and undergone numerous changes in an effort of keeping up with international expectations, regulatory initiatives and competitive pressures. On the one hand, banks have been diversifying their activities in pursuit of customising their services to industries’ needs to increase their risk resilience and secure their marginal returns. On the other hand, they have been engaging in investments within the wider field of Corporate Social Responsibility (CSR). The underlying value proposition of this mandate rests upon facilitating and further strengthening mutually beneficial relationships with the society while recognising the delicate balance and preservation of the natural environment. In this direction, many banks in the last decades tried to ensure their image through investments in the field of culture. The present research explicates the manifestation and operationalisation of CSR through investment realised for cultural objectives as part of the social aspect business responsibility. As such, we shift attention towards practices applied worldwide by the banking sector with respect to museums. Furthermore, we abide by a single case study approach and investigate the business model of the Cultural Foundation of Piraeus Bank (CFPB) as a CSR practice. Piraeus Bank is the largest commercial bank in Greece and CFPB constitutes a unique paradigm worldwide, since the bank not only contributes to the establishment of the museum in line with the majority of other banking initiatives that witness support through sponsorships but it is also actively engaged in its ongoing operations. The network of CFPB includes currently nine thematic museums in several locations throughout Greece. In light of these, we present how CFPB aligns and realises its activities in terms of financing, relationships between its network of museum with local communities as well as the promotional strategies deployed. Finally, we also discuss on potential future research avenues and implication derived for both academia and practice.